Secrets of plants: Endophytes (International Journal of Plant Biology, 2018)
Endophytic fungi are an important component that colonizes in healthy tissues of living plants and can be readily isolated from any microbial or plant growth medium. They act as reservoirs of novel bioactive secondary metabolites, such as alkaloids, phenolic acids, quinones, steroids, saponins, tannins, and terpenoids that serve as a potential candidate for antimicrobial, anti-insect, anticancer and many more properties. Their huge diversity and particular habituation, they can provide a good area for research in the field of making new medicines and novel drug-like molecules. Because of the impact of endophytes on host plant by enhancing their growth or increasing their fitness, also making them tolerant to abiotic and biotic stresses and holding the secondary metabolites, endophytes are gaining attention as a subject for research. This review aims to comprehend the contribution and uses of endophytes and relationships between endophytic fungi and their host medicinal plants.